2011
DOI: 10.1200/jco.2010.32.8146
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin Use and the Risk of Breast Cancer in Women

Abstract: Women currently using digoxin had a significantly increased risk of breast cancer. Risk normalized when digoxin was stopped. No risk increases were observed in women using angina drugs only. The higher risk of developing ER-positive breast cancers supports an estrogen-mimicking mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 29 publications
5
62
1
Order By: Relevance
“…Our analyses provide some reassurance that digoxin may be safe in women with breast cancer, despite the potential estrogenic effect of this drug and other observational evidence that it may increase breast cancer risk [1,[7][8][9]. Our analyses also did not show strong evidence of reductions in cancer-specific mortality in digoxin users and therefore does not support the findings of preclinical studies which suggest that digoxin has inhibitory effects on breast cancer cell growth [20][21][22][23].…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Our analyses provide some reassurance that digoxin may be safe in women with breast cancer, despite the potential estrogenic effect of this drug and other observational evidence that it may increase breast cancer risk [1,[7][8][9]. Our analyses also did not show strong evidence of reductions in cancer-specific mortality in digoxin users and therefore does not support the findings of preclinical studies which suggest that digoxin has inhibitory effects on breast cancer cell growth [20][21][22][23].…”
Section: Discussioncontrasting
confidence: 63%
“…Consequently, a number of epidemiological studies have shown increases in breast cancer risk in digoxin users. For instance, two Danish studies have shown approximately 35 % increases in breast cancer risk in digoxin users versus non-users [8,10] and a US study observed a 45 % increase in breast cancer risk [7]. These observed increases in breast cancer risk in digoxin users raise questions about the safety of digoxin use in breast cancer patients.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, 2 studies in Denmark reexamined breast cancer risk in women using digoxin (1,2), the only digitalis drug in the Danish formulary. Using large data sets, both studies reached similar conclusions: The risk was significantly increased.…”
Section: Digitalis and Cancer Riskmentioning
confidence: 99%
“…Both forms are phyto-estrogens, or plant estrogens. Recent studies have shown that use of digoxin significantly increases the risk of breast and uterus cancer (1)(2)(3). Both cancers are often estrogen sensitive.…”
Section: Introductionmentioning
confidence: 99%